Learned fear to social out-group members are determined by ethnicity and prior exposure - Golkar, Armita; Björnstjerna, Marie; Olsson, Andreas (Frontiers in Psychology, 2015)
Humans, like other animals, have a tendency to preferentially learn and retain some associations more readily than others. In humans, preferential learning was originally demonstrated for certain evolutionary prepared stimuli, such as snakes and angry faces and later extended to human social out-groups based on race (Olsson, Ebert, Banaji, & Phelps, 2005). To address the generality of this social learning bias, we examined if this learning bias extended to two separate classes of social out-groups represented by neutral Black and Middle-Eastern faces in 38 White, (Swedish) participants. We found that other-ethnicity alone was not sufficient to induce an out-group learning bias; it was observed for Black, but not Middle-Eastern, out-group faces. Moreover, an exploratory analysis showed that growing up in an ethnically diverse environment was inversely related to the learning bias towards Middle-Eastern, but not Black, out-groups faces, suggesting that learned fears towards Middle-Eastern faces might be more permeable to environmental factors. Future research should address how both the quantity and quality of inter-group contact modulate out-group learning.